Imaging of Unstained DNA Origami Triangles with Electron Microscopy. Issue 12 (13th August 2019) - Londono‐Calderon, Alejandra; Hossen, Md Mir; Palo, Pierre E.; Bendickson, Lee; Vergara, Sandra; Nilsen‐Hamilton, Marit; Hillier, Andrew C.; Prozorov, Tanya
Abstract: Imaging of scaffolded DNA and DNA origami nanostructures has been dominated by atomic force microscopy of samples immobilized on bulk substrates. Less commonly used are electron microscopy techniques, typically carried out after negative staining of DNA structures or by using cryo‐transmission electron microscopy (TEM). Here, direct imaging of unstained DNA origami on common electron‐transparent substrates with utilizing high angular annular dark field scanning transmission electron microscopy (HAADF‐STEM) is reported. This approach establishes a method for depositing and imaging intact DNA triangles with mass‐thickness contrast sufficient to measure the scaffold‐to‐scaffold distances and the length of the triangle's seam. The signal‐to‐noise ratio (SNR) of the DNA supported on amorphous carbon as a function of the carbon thickness is measured on three types of commercially available TEM grids. This allows for edge detection of ≈1 nm height DNA triangles on carbon substrates as thick as ≈25 nm. Observations on the effect on SNR with the imaging modes are discussed. The effect of cation concentration used for pretreating the grid on the image resolution is also explored. This work presents proof‐of‐concept results demonstrating that electron microscopy can be used to resolve key elements of the DNA origami triangle without the use of staining protocols. Abstract : Direct imaging of visibly intact DNA origami triangles with scanning transmission electron microscopy is presented. DNA is deposited on commercially available electron microscopy grids and imaged in high angular annular dark field scanning transmission electron microscopy (HAADF‐STEM) mode without the use of staining agent. The signal‐to‐noise ratio of the DNA triangles on an ultrathin carbon substrate is sufficient to resolve the scaffold‐to‐scaffold distance in the triangle's design.